Optimized encapsulation of bis-ethylhexyloxyphenol methoxyphenyl triazine (BEMT) in porous silica for enhanced UV protection and stability - Dong, Xue; Woo, Chaeheon; Lee, Myunghee; Shin, Kyounghee; Yu, Hak Ki; Choi, Jae-Young (Elsevier BV, 2025)
The stability and effectiveness of organic UV filters remain key challenges in sunscreen formulations due to their potential for degradation and skin penetration. In this study, we developed a BS@SiO2-30 % composite, in which bis-ethylhexyloxyphenol methoxyphenyl triazine (BEMT) was encapsulated within a porous SiO2 matrix and coated with a hydrophilic SiO2 layer. This encapsulation process enhanced photostability, and formulation compatibility while preventing skin penetration of BEMT. The composite exhibited an SPF value of 41.75, significantly surpassing the control, demonstrating superior UV protection. Additionally, stability tests confirmed that the hydrophilic SiO2 coating facilitated even dispersion in aqueous formulations, addressing the limitations of conventional UV filters. These findings highlight the potential of SiO2-based encapsulation as an effective strategy for improving organic UV filters, paving the way for next-generation, high-performance, and photostable sunscreen formulations.